Sperm retrieval rates in non‐mosaic Klinefelter patients undergoing testicular sperm extraction: What expectations do we have in the real‐life setting?. (16th February 2020) - Boeri, Luca; Palmisano, Franco; Preto, Mirko; Sibona, Mattia; Capogrosso, Paolo; Franceschelli, Alessandro; Ruiz‐Castañé, Eduard; Sarquella‐Geli, Joaquim; Bassas‐Arnau, Lluís; Scroppo, Fabrizio Ildefonso; Saccà, Antonino; Gentile, Giorgio; et al.
Abstract: Background: A recent meta‐analysis ( Human Reproduction Update 23, 2017 and 265) reported positive sperm retrieval rates (SRR) in 50% of patients with Klinefelter syndrome (KS) undergoing testicular sperm extraction (TESE). However, these results do not reflect the rates of SR that we observe in clinical practice. We assessed the rate and potential predictors of SR in Klinefelter patients in the real‐life setting. Materials and Methods: We reviewed clinical data of 103 KS men who underwent TESE between 08/2008 and 03/2019 at five tertiary referral Andrology centers. Patients underwent testis ultrasound, hormonal evaluation, and genetic testing. All patients were azoospermic based on the 2010 WHO reference criteria. Conventional TESE (cTESE) or microsurgical TESE (mTESE) was performed based on the surgeon's preference. We used descriptive statistics and logistic regression models to describe the whole cohort. Results: Median (IQR) patient's age was 32 (24‐37) years. Baseline serum FSH and total testosterone levels were 29.5 (19.9‐40.9) mUI/mL and 3.8 (2.5‐11.0) ng/mL, respectively. Conventional TESE and mTESE were performed in 38 (36.5%) and 65 (63.5%) men, respectively. The sperm retrieval rate was 21.4% (22/103 men). Fifteen patients used spermatozoa for ICSI and five ended in live birth children. Patients with positive SR were similar to those with a negative TESE in terms of clinical, hormonal, and procedural parameters (all P > .05). Logistic regression analyses confirmed the lack of association between clinical, hormonal, and procedural parameters with SR outcome. Discussion: Given the conflicting results in the literature regarding SRR in KS, patients should be carefully counseled regarding TESE outcomes based on data from published literature and local results. Conclusions: In the real‐life setting, we observed a lower SRR (21.4%) than that reported in meta‐analyses in our cohort of KS patients. No associations between clinical, hormonal, and procedural variables with TESE success were found.